Aggressive Tax Planning in the Post-BEPS Era : Systematic Approach with Analysis and Examples - Knuutinen, Reijo; Itälä, Hannu (Nordic Tax Research Council, 2026)
Aggressive tax planning (ATP) does not have any legal definition or any other precise and established definition. Nor is it intended here to define precisely ATP. Instead, the primary purpose is to create a more general reference framework for aggressive tax planning after the base erosion and profit shifting (BEPS) project of the OECD and G20 countries. Some situations or means of ATP have been left outside the scope of the BEPS project. In some cases, various occurrences of ATP are not covered by the implemented regulation, that is, the regulation can be considered underinclusive. Further, some of the proposed means are such that even though precise regulation has been targeted at these situations, the regulation has been implemented in such a way that its ultimate purpose can be circumvented. Finally, various ATP methods can rely on the fact that different states have not fully implemented the BEPS recommendations. The proposed framework can serve as a tool and incentive for both current and future tax policy discussions. Locating concrete ATP activities in the reference framework also illustrates for whom it would be possible and with what kind of legislative means to intervene in such phenomena.